SOCIAL REFORMS IMPLEMENTED DURING THE REIGN OF MANGITS IN THE WORK OF "HISTORY OF KHUMULI" (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article discusses the educational system established in cities such as Bukhara and Samarkand. In particular, the information about the transformation of these cities into centers of science during the Mangit era is analyzed and revealed based on historical sources. In addition, information about the educational institutions that were reopened as a result of economic, socio-political reforms in the Bukhara emirate, and the appointment of teachers and mentors to them is provided. Also, the reforms carried out in Samarkand during this period, in particular, educational reforms, are analyzed based on the work "Tarihi Khumuliy", which is considered an important historical source. The article also discusses the work "Tarihi Khumuliy", its author, and the issues covered in it.